Anti-Plastic Waste Campaign: Education and Reduction of Plastic Use for Communities and Businesses - Suprapto, Suprapto; Kwarto, Febrian; Kaidah, Sri (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2025)
In South Meruya Village, West Jakarta, the urgency of plastic waste management is increasingly heightened alongside continuous population growth and urbanization. The accumulation of plastic waste poses serious threats to ecosystem integrity and public health, exacerbated by deficient community awareness and inadequate waste management infrastructure. This anti-plastic waste campaign initiative aims to enhance public understanding of the potential dangers posed by plastic, promote reduction of single-use plastic consumption, and optimize community-based plastic waste management systems. Implementation strategies include intensive education programs, provision of economically affordable eco-friendly alternatives, strengthening of recycling infrastructure, and enforcement of regulations related to plastic bag reduction. Expected outcomes from this initiative include increased active community participation in recycling programs, significant reduction in single-use plastic consumption, establishment of sustainable waste management systems, and creation of a cleaner environment conducive to health in South Meruya Village. The success of this campaign is expected to be replicable as a model for other regions in addressing plastic waste issues.